2005
DOI: 10.2337/diabetes.54.1.190
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Accelerated Rates of Glutathione Utilization and Glutathione Depletion in Adolescents With Poorly Controlled Type 1 Diabetes

Abstract: Depletion of glutathione, an important antioxidant present in red cells, has been reported in type 1 diabetes, but the mechanism of this depletion has not been fully characterized. Glutathione depletion can occur through decreased synthesis, increased utilization, or a combination of both. To address this issue, 5-h infusions of L-[3,3-2 H 2 ]cysteine were performed in 16 diabetic adolescents divided into a well-controlled and a poorly controlled group and in eight healthy nondiabetic teenagers as control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 32 publications
6
64
0
1
Order By: Relevance
“…The ranges are not caused by outliers but are caused by variation of glutathione FSR within the population. Although the range of fractional synthesis rates is between 30 and 70%/d, the SD is low in both groups compared with similar studies conducted by others (8,39,40).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The ranges are not caused by outliers but are caused by variation of glutathione FSR within the population. Although the range of fractional synthesis rates is between 30 and 70%/d, the SD is low in both groups compared with similar studies conducted by others (8,39,40).…”
Section: Discussionsupporting
confidence: 63%
“…GSH is a tripeptide consisting of the amino acids (AA) glutamate, cysteine, and glycine. It is synthesized in virtually every tissue but is mainly produced in liver and erythrocytes with erythrocytic concentrations being in the millimolar range (8). Erythrocytes are suggested to function as antioxidant defense by being a physiologic source of GSH and by taking up ROS (9,10).…”
mentioning
confidence: 99%
“…GPx depletion may have a major role in the pathogenesis of vascular complications and microalbuminuria with increased oxidative stress. 36 In a study by Yoshimura et al 37 GPx was found to be localized diffusely in the cytoplasm of hepatocytes in the liver of rats. Additionally, periportal area had more intense staining than the centriobular area, and no staining was reported in endothelial cells around the sinusoids and in Kupffer cells.…”
mentioning
confidence: 95%
“…Decrease of GPx levels, which is among antioxidant enzymes, is thought to be occurred due to inactivation of antioxidant enzymes as a result of glycation caused by hyperglycemia in diabetes. 42 GPx depletion may have a major role in the pathogenesis of vascular complications and microalbuminuria with increased oxidative stress. 43 In a study by Yoshimura et al 44 GPx was found to be localized diffusely in the cytoplasm of hepatocytes in the liver of rats.…”
Section: Discussionmentioning
confidence: 99%